ANALISA LAPORAN AUDIT (STUDI KASUS BANK BUMN) - Zulkifli Z; Fiona Natasha Angelina; Yohana Stefany Suprianto (JURNAL ILMIAH EDUNOMIKA, 2022)
This research aims to maintain the result of auditing report analysis in pandemic era which has not over yet since Februari 2020. The effect of this pandemic was a difficulty in determining the ability of a company to prepare audit reports. This research is finding out whether there is the effect of state-owned enterprise financial report in pandemic era in order to anticipate possible impact that may occur in the future during this pandemic. This research uses library research methods and quantitative descriptive methods. It can concluded that the five state-owned banks’ financial statement show the accompanying consolidated financial statements are presented fairly.